Candida Biofilms: An Update on Developmental Mechanisms and Therapeutic Challenges - de Barros, Patrícia Pimentel [UNESP]; Rossoni, Rodnei Dennis [UNESP]; de Souza, Cheyenne Marçal [UNESP]; Scorzoni, Liliana [UNESP]; Fenley, Juliana De Camargo [UNESP]; Junqueira, Juliana Campos [UNESP] (Springer Nature, 2020)
Fungi of the genus Candida are important etiological agents of superficial and life-threatening infections in individuals with a compromised immune system. One of the main characteristics of Candida is its ability to form highly drug tolerance biofilms in the human host. Biofilms are a dynamic community of multiple cell types whose formation over time is orchestrated by a network of transcription regulators. In this brief review, we provide an update of the processes involved in biofilm formation by Candida spp. (formation, treatment, and control), as well as the transcriptional circuitry that regulates its development and interactions with other microorganisms. Candida albicans is known to build mixed species biofilms with other Candida species and with various other bacterial species in different host niches. Taken together, these properties play a key role in Candida pathogenesis. In addition, this review gathers recent studies with new insights and perspectives for the treatment and control of Candida biofilms.
Keywords: Alternative treatment; Biofilms; Candida spp; Polymicrobial biofilms; Transcriptional circuitry